Indonesia's Role in Protecting High Seas Biodiversity: Challenges and Opportunities in Light of the Biodiversity Beyond National Jurisdiction Treaty - Wati, Erna (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research paper is a product of a doctrinal legal study that examines Indonesia's role in addressing challenges and opportunities related to marine biodiversity protection in international waters. As a leading maritime nation, Indonesia plays a crucial role in global efforts to protect ocean health, especially in the face of increasing threats such as overfishing, pollution, and climate change. These issues are regulated in international legal frameworks such as the United Nations Convention on the Law of the Sea (UNCLOS) and the Biodiversity Beyond National Jurisdiction (BBNJ) Treaty of 2023. By using a normative legal study approach, this study analyses international treaties, conventions, and academic literature to evaluate the application of the